(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present paper is based on the research conducted to find out not only the leadership behaviour of school principals but also to identify some of the behavioural characteristics which may be detrimental in improving the school performance while comparing the principal leadership behaviour of high performing and low performing schools. Two factors namely gender (malefemale) and type of school (Govt. Private) were also taken to provide some insight into whether or not the two make a difference in one or more factors of principal leadership behaviour. In order to uncover the most important factors of leadership behaviour of principal which might be detrimental to school performance, the present study not only attempted to identify the association between the two but also t the extent to which principal leadership behaviour and its different factors contributes in the school performance. The study has found not only a significant positive relationship between principal leadership behaviour and school performance but also a significant difference in the principal leadership behaviour of high-performing and low-performing schools resulting into the evidence of significant impact of principal leadership behaviour, in terms of the two construct namely transformational leadership and passive avoidant leadership, on school performance.